PENERAPAN METODE DRILL DALAM PEMBELAJARAN MENULIS TEKS EDITORIAL - Hidayah, Nurul Aulia; Sumiati, Ati; Saktiyani, Aurelia (IKIP Siliwangi, 2019)
This research is based on the existence of students who experience difficulties in learning to write editorial texts, it is based on student evaluation data that is still not optimal in writing editorial texts, this is contrary to the innovation of learning methods used by teachers, to improve this research using application learning methods innovative, drill method. The method of drill or ready training is a method that can improve writing skills, so that it can be developed into a complete work. This study discusses improving students 'abilities in learning to write editorial texts, thus making the authors formulate the following problems: Is it necessary to improve students' ability to learn to write editorial texts using the drill method? This study uses the Pre-Experimental Design method with the design form of One-Group Pretest-Posttest Design. Based on the results of the study. Improving the ability of students to write editorial texts using the drill method. Based on the calculation of the hypothesis t test using the SPSS 21.0 program obtained the results of tcount (7,519) abel t table (1,734). This shows that Ha is accepted and H0 is rejected. Drill method proved effective in learning to write editorial texts.